Implementation of Literacy Culture in Developing Civic Intelligence of Grade VII Students of Smp Negeri 1 Bilah Hulu - Harahap, Siti Holiza; Junita, Junita; Anjar, Agus (Jurnal Riset Ilmu Pendidikan, 2024)
This research aims to explore the implementation of literacy culture among class VII students at SMP Negeri 1 Bilah Hulu and its influence on the development of students' civic intelligence. The literacy culture in question includes reading, writing and discussion activities which aim to increase students' insight and skills in understanding social, political and civic issues. This research also identifies factors that support and hinder the implementation of literacy culture in schools, as well as their impact on the development of students' civic intelligence. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Research subjects included class VII students, teachers, and related parties at SMP Negeri 1 Bilah Hulu. The data obtained was analyzed using thematic analysis techniques to identify the main themes in the implementation of literacy culture and its relationship with the development of civic intelligence. The research results show that the implementation of literacy culture at SMP Negeri 1 Bilah Hulu has been implemented well, although there are several challenges, such as a lack of literacy facilities and limited time for literacy activities. Factors that support the implementation of a literacy culture include support from the school, availability of reading materials, and active participation of teachers in guiding students. On the other hand, inhibiting factors include students' lack of interest in reading and limited time for carrying out literacy activities. The literacy culture implemented has been proven to have a positive influence on the development of students' civic intelligence, which can be seen from students' increased understanding of their rights and obligations as citizens, as well as their involvement in discussions and social activities that support civic values.